Revenue income vs capital receipt: the validity of the basis for taxing receipts from mining operators in the hands of landowners - Krige, André Claude (Department of Finance and Tax, 2020)
During the 1980’s and onwards, the Western Cape’s Tax and High Courts were inundated with cases relating to the capital vs revenue classification on receipts by landowners from mining operators. These cases became known, in the common parlance, as the Cape Sand Cases. The principles debated during these hearings, range from “corpus vs fructus” to “single transactions vs carrying on a trade” and “capital disposal vs productively employing a capital asset”. The general principles formed during the rulings on these cases, fell largely in favour of the tax authorities and served as a deterrent to taxpayers for incessantly challenging the status quo on the classification of receipts from similar sources. Recent review of contracts within the industry and landowner consideration for classifying income, still follow the guidance of these common law principles. This study examines some of these past cases to get a better understanding of the reasoning which has led to the outcomes previously derived. An assessment of the changes introduced to tax legislation is made in order to provide grounds for the potential deflection from the incumbent perceptions on the classification of receipts. The initial investigation leads to the focal point of this study, which is the introduction of the MPRDA (Mineral and Petroleum Resources Development Act, 2002). Relying on the MPRDA, along with court cases challenging some of its content, the position of landowners is distinguished from that held during the formation of the common law on the classification of their income. The common law principles are challenged and reasons given, for denying exclusive reliance on previous case law when adjudicating the classification of income. This study, along with possible restructuring of the contracts that underlie these transactions, serves as basis for challenging the current classification of income by landowners from mining operators, previously deemed to be revenue in nature.